Military activity of akyn-zhyrau in the period of the Kazakh khanate (Journal of history, 2019)
This article is devoted to the military activities and contribution of akyn-zhyrau in military activities and art of Kazakh people during the Kazakh Khanate relying on their performances as a historical source. As the representatives of the class warriors they engaged in military activities and knew all the details of this profession. Akyn-zhyrau poetry is a rich source to study military art, military equipment, method of their use, professional terms, customs and traditions of men. During the Kazakh Khanate works of Akyn-zhyrau are closely linked to the military science and the art of the Kazakh people. The period of the Kazakh Khanate is the heroic period, period of brave men. Akyn-zhyrau is not only extolled the heroism of brave men, but they themselves took part in the battles with the enemy, they are not only soldiers singers, they were warlords and commanders